Analysis of the relationship between low-grade inflammation markers and the severity of atherosclerotic coronary bed lesions - A. V. Ushakov; E. A. Zakharyan; P. E. Grigoriev; K. D. Malyi (Бюллетень сибирской медицины)
Aim. To study serum concentrations of low-grade inflammation markers and the severity of atherosclerotic processes in the coronary artery in patients with coronary heart disease (CHD) in the context of their clinical and instrumental characteristics. Materials and methods. The study included 264 participants (161 men and 103 women), with 220 of them being diagnosed with CHD. Subgroups were identified among the participants, including those with a history of myocardial infarction (110 patients) and angina pectoris (152 patients). A control group consisted of healthy volunteers (44 persons). The patients underwent coronary angiography, echocardiography, duplex ultrasound scanning of the extracranial segments of the brachiocephalic arteries. The level of C-reactive protein (CRP (mg/L)), tumor necrosis factor alpha (TNF-α (pg/ml)), growth differentiation factor 15 (GDF-15 (pg/ml)), and endothelial cell specific molecule-1 (ESM-1 (ng/ml)) in the blood serum were measured. Statistical significance was considered at p < 0.05. Results. A significantly higher concentration of all laboratory markers of low-grade inflammation in the CHD group of patients compared to the control group, as well as a significant increase in their values with enhance in the severity of coronary atherosclerosis (p<0.0001) was found. Significant differences in marker levels were also found between patients with angina pectoris and a history of myocardial infarction compared to those without these conditions. A correlation was revealed between the value of markers and various clinical and instrumental characteristics of the patients. Multivariate linear regression analysis revealed a statistically significant association of SYNTAX score with the concentration of GDF-15 and ESM-1, but not with CRP and TNF-α. Conclusions. The simultaneous measurement of multiple laboratory parameters may be a more effective method for assessing the risk of CHD progression. The study also showed that endocan and GDF-15 have high prognostic significance in evaluating the severity of atherosclerotic processes in the coronary arteries.